Gastrointestinal manifestations of Henoch-Schonlein purpura: A report of two cases - Prathiba Rajalakshmi, Parameswaran (World J Radiol, 2015)
Henoch-Schonlein purpura (HSP) is a small vessel vasculitis mediated by type III hypersensitivity with deposition of IgA immune complex in the walls of vessels. It is a multi-system disorder characterized by palpable purpura, arthritis, glomerulonephritis and gastrointestinal manifestations and commonly occurs in children and young adults. The patients with gastrointestinal involvement usually present with colicky abdominal pain, vomiting and melena. The imaging findings include multifocal bowel thickening with mucosal hyperenhancement, presence of skip areas, mesenteric vascular engorgement, with involvement of unusual sites like stomach, duodenum and rectum. These imaging findings in a child or young adult with appropriate clinical findings could suggest HSP.